Development of Interactive E-Books containing Virtual Laboratory to Improve Students’ Motivation Learning - Ramadhani, Viola Yorika; Khusniati, Miranita (Journal of Environmental and Science Education, 2022)
This study aims to analyze the characteristics, validity, and ability of Interactive E-Book media containing Virtual Laboratory in fostering learning motivation and to find out how the cognitive learning outcomes of students. The design of this research is Research and Development, using modified steps according to Sugiyono. Analysis of potential problems seen from the low motivation to learn of students, which is supported by the lack of innovation in learning media on global warming at SMP N 4 Semarang. In this study, an interactive learning media on global warming material was developed in the form of an E-Book with an application format so that it could be accessed flexibly via mobile phones. The Interactive E-Book was declared very valid with an average validation of 92.94% from media validators and 89.87% from material validators. Then a trial was conducted to determine the readability of the media. The results of the media readability research from students obtained an average of 88.92% with very good criteria. The ability of Interactive E-Books to increase students' learning motivation was measured using a learning motivation questionnaire, there was an increase in the high category. In addition, the increase in learning motivation is also supported by the cognitive learning, average pretest score was 51.78 while the posttest score was 85.56. Based on the description, it is concluded that the Interactive E-Book is valid to be used as a medium in learning activities and is able to improve students' learning motivation.